Advances in Nanoelectronics: Carbon Nanotubes, Graphene, and Smart Polymers: A review - Kianfar, Ehsan (Trends in sciences, 2025)
In recent years, in order to miniaturize electronic devices, reduce manufacturing costs and increase the efficiency of electronic and optical systems, a new field called “nanoelectronics” has been developed. In this field, silicon is no longer used as the main component of systems, and this unique material has given its place to biological, organic and mineral materials. For this reason, the general principles of design in nanoelectronics devices are subject to new parameters, each of which can lead to the development of new properties, characteristics and applications. Nanoelectronics science seeks to miniaturize traditional electronic devices and increase their efficiency. So far, a comprehensive classification for the main sub-branches of nanoelectronics that all scientific authorities follow has not been provided. However, nanoelectronics can be considered in several broad areas: 1) Nano sensors; 2) lab-on-a-chip; 3) artificial organs; 4) bionics and biomimetic; 5) imaging; 6) integrated circuits and 7) molecular nanoelectronics. Organic materials are those materials that have a continuous structure of carbon-hydrogen bonds. So far, more than 16 thousand types of organic substances with different molecular and chemical structures have been produced. One of the main applications of this category of materials is their use in the manufacture of nanoelectronic devices. In this way, a field in electronics called “organic nanoelectronics” has been developed. But so far, only a limited number of these materials have been able to be used in organic-based nanoelectronics devices. These materials include: organic charge transfer complexes, conductive or conjugated polymers with π bonds, conductive gels, and dielectric polymers. The reason for the importance of each of these types of materials is their electrical properties and unique structure. Carbon nanotube is used in many nanoelectronics devices due to its crystallographic structure and unique properties. Due to its significant surface area, hollow structure, high mechanical strength, excellent electrical properties, and unique structures in electron bonds, this material is widely used in energy storage, nanocomposite materials, and making nanoelectronics devices such as Nano sensors. HIGHLIGHTS Investigating Electrical properties of carbon nanotubes. Investigating Applications of nanoelectronics in the structure of carbon nanotubes. Investigating Electrical properties of graphene. Investigating Applications of graphene in nanoelectronics. Investigating Chemical composition of organic Materials. Investigating Advantages of organic materials in nanoelectronics. Investigating Electro biochemical principles governing nanoelectronics. Investigating The main sub-branches in the field of nanoelectronics. GRAPHICAL ABSTRACT